KONSELING MENINGKATKAN PERILAKU IBU DALAM PENCEGAHAN DAN PERAWATAN BALITA INFEKSI SALURAN PERNAFASAN AKUT DI WILAYAH KERJA PUSKESMAS BANGKALAN - Khotimatul Husna; Ninuk Dian Kurniawati; Nuzul Qur'aniati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Acute respiratory infection (ARIs) is acute infection attacks human respiratory tract. The disease becomes one of the public health problems in Indonesia especially for under-five children. One of the causes of ARI is unsuitable in preventing and caring behavior. It needs special attention because of high disease number in puskesmas. Health education which has been done isspeech method to many people. But personal counseling method has never done. The study aims to analyze behavior of mother in preventing and caring ARI in children under-five in working area Puskesmas Bangkalan.Methods: This research used quasy experimental design and population mother who had children with acute respiratory infection. The sampling used purpossive sampling technique, based on inclusion criteria, used 32 mothers consist of 16 people as experiment group and 16 people as control group. Data collected by questioner and analysed by wilcoxon signed rank test and mann whitney test with significant value p≤0.05. Results: The result statistically showed there was difference between pre and post for knowledge (p=0.025), attitude (p=0.007), and action (p=0.001) in experiment group and there was difference between control and experiment group for knowledge (p=0.007), attitude (p=0.005), and action (p=0.003).Discussion: The results concluded that counselling had effect to preventing and caring behavior of mother in working area Puskesmas Bangkalan. Suggestion for next researcher is we need further experiment about effect of counselling to mother’s behavior using other research method in order to generalizethe result